Object categorization by wild ranging birds-Winter feeder experiments - Nováková, Nela; Veselý, Petr; Fuchs, Roman (Behavioural processes, 2017)
The object categorization is only scarcely studied using untrained wild ranging animals and relevant stimuli. We tested the importance of the spatial position of features salient for categorization of a predator using wild ranging birds (titmice) visiting a winter feeder. As a relevant stimulus we used a dummy of a raptor, the European sparrowhawk (Accipiter nisus), placed at the feeding location. This dummy was designed to be dismantled into three parts and rearranged with the head in the correct position, in the middle or at the bottom of the dummy. When the birds had the option of visiting an alternative feeder with a dummy pigeon, they preferred this option to visiting the feeder with the dummy sparrowhawk with the head in any of the three positions. When the birds had the option of visiting an alternative feeder with an un-rearranged dummy sparrowhawk, they visited both feeders equally often, and very scarcely. This suggests that the titmice considered all of the sparrowhawk modifications as being dangerous, and equally dangerous as the un-rearranged sparrowhawk. The position of the head was not the most important cue for categorization. The presence of the key features was probably sufficient for categorization, and their mutual spatial position was of lower importance.
Keywords: podněty; Cues; Animals, Wild; Avoidance Learning; Passeriformes; stravovací zvyklosti; učení vyhýbat se; divoká zvířata; Animals; některé rody čeledi Accipitridae; zvířata; Hawks; Feeding Behavior